The (socio) politics of misfit: a moderated-mediation model. Issue 2 (2nd March 2021) - Zubielevitch, Elena; Cooper–Thomas, Helena D.; Cheung, Gordon W.
Abstract : Purpose: The growing instability of the labor market will almost certainly result in more employees whose values misfit with their organization's. This paper draws from the exit-neglect-voice-loyalty model to examine a broader range of responses to misfit; explores sociopolitical resources as the mechanisms through which misfit transmits its effects and investigates job mobility as a boundary condition enhancing or constraining responses to misfit. Design/methodology/approach: A novel model ( N = 152 New Zealand employees) examined links from misfit to two sociopolitical resources (perceived influence and organizational responsiveness) and from these to exit-neglect-voice-loyalty moderated by job mobility. Supplemental analyses examine moderated-mediation. Findings: Misfit negatively predicted both sociopolitical resources, perceived influence and organizational responsiveness. Moderated-mediation analyses showed that the constructive reactions to misfit (voice and loyalty) were predicted conditionally at low levels of job mobility and indirectly via the respective sociopolitical resources. In contrast, destructive reactions to misfit (exit and neglect) were predicted directly, with neglect predicted at high levels of job mobility. Research limitations/implications: Implications for human resource practitioners highlight the deleterious repercussions of misfit but also include the conditions under which misfit employees may attempt to constructively salvage their employment relationship. Originality/value: This study integrates a broader set of concurrent responses to misfit using the exit-neglect-voice-loyalty typology, as well as introducing sociopolitical perspectives to the literature on misfit.